Paliurus spina-christi Mill fruit extracts improve glucose uptake and activate the insulin signaling pathways in HepG2 insulin-resistant cells - Seyedeh Mona Mousavi Esfahani; Parastoo Tarighi; Kosar Dianat; Tabarek Mahdi Ashour; Negar Mottaghi-Dastjerdi; Mehdi Aghsami; Mahsa Sabernavaei; Hamed Montazeri (BMC, 2023)
Abstract Background Paliurus spina-christi Mill. (PSC) fruit is frequently used in the treatment of diabetes mellitus in Mediterranean regions. Here, we investigated the effects of various PSC fruit extracts (PSC-FEs) on glucose consumption and some key mediators of insulin signaling pathways in high glucose and high insulin-induced insulin-resistant HepG2 cells. Methods The effects of methanolic, chloroform and total extracts on cell proliferation were assessed by the MTT assay. The potential of non-toxic extracts on glucose utilization in insulin-resistant HepG2 cells was checked using a glucose oxidase assay. AKT and AMP-activated protein kinase (AMPK) pathway activation and mRNA expression levels of insulin receptor (INSR), glucose transporter 1 (GLUT1), and glucose transporters 4 (GLUT4) were determined by western blotting and real-time PCR, respectively. Results We found that high concentrations of methanolic and both low and high concentrations of total extracts were able to enhance glucose uptake in an insulin-resistant cell line model. Moreover, AKT and AMPK phosphorylation were significantly increased by the high strength of methanolic extract, while total extract raised AMPK activation at low and high concentrations. Also, GLUT 1, GLUT 4, and INSR were elevated by both methanolic and total extracts. Conclusions Ultimately, our results shed new light on methanolic and total PSC-FEs as sources of potential anti-diabetic medications, restoring glucose consumption and uptake in insulin-resistant HepG2 cells. These could be at least in part due to re-activating AKT and AMPK signaling pathways and also increased expression of INSR, GLUT1, and GLUT4. Overall, active constituents present in methanolic and total extracts of PCS are appropriate anti-diabetic agents and explain the use of these PSC fruits in traditional medicine for the treatment of diabetes.